2021
DOI: 10.3390/cancers13143414
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Composition of Serum-Derived Small Extracellular Vesicles in Participants of a Lung Cancer Screening Study

Abstract: Molecular components of exosomes and other classes of small extracellular vesicles (sEV) present in human biofluids are potential biomarkers with possible applicability in the early detection of lung cancer. Here, we compared the lipid profiles of serum-derived sEV from three groups of lung cancer screening participants: individuals without pulmonary alterations, individuals with benign lung nodules, and patients with screening-detected lung cancer (81 individuals in each group). Extracellular vesicles and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 45 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…It is important to highlight the fact that each of these miRNA species has a role connected to cancer and has been linked to the progression of lung cancer. In addition, a handful of them, including recognized oncomirs miR-17, miR-19, miR-21, and miR-221, emerged in many miRNA signatures of lung cancer based on both the total serum/plasma and serum/plasma-derived EVs (148). Another group demonstrated that macrophage migration inhibitory factor, or MIF, was significantly expressed in EVs formed from pancreatic ductal adenocarcinomas (PDAC), and that blocking MIF inhibited the establishment of a pre-metastatic niche in the liver as well as metastasis.…”
Section: Different Types Of Evs and Their Roles In The Light Of Bioma...mentioning
confidence: 99%
“…It is important to highlight the fact that each of these miRNA species has a role connected to cancer and has been linked to the progression of lung cancer. In addition, a handful of them, including recognized oncomirs miR-17, miR-19, miR-21, and miR-221, emerged in many miRNA signatures of lung cancer based on both the total serum/plasma and serum/plasma-derived EVs (148). Another group demonstrated that macrophage migration inhibitory factor, or MIF, was significantly expressed in EVs formed from pancreatic ductal adenocarcinomas (PDAC), and that blocking MIF inhibited the establishment of a pre-metastatic niche in the liver as well as metastasis.…”
Section: Different Types Of Evs and Their Roles In The Light Of Bioma...mentioning
confidence: 99%
“…Significant differences in EVs and serum lipid profiles were also observed. 91 Accordingly, these researches have demonstrated the sensitivity of metabolic markers to clarify malignant cancer, especially for highly heterogeneous nodules when using low-dose computed tomography (CT). However, more information and tests are needed to promote the availability of the technology.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...mentioning
confidence: 99%
“… Diagnosis Late myocardial necrosis of atherosclerotic Adipose tissue C16:0 ceramide and their derivatives [ 87 ] Acute pancreatitis Plasma Eicosatrienoic acid (C20:3), thiamine triphosphate. 2-Acetylfuran, cis-Citral [ 68 ] Gestational hypertension Plasma SM, acetyl CoA, methionine, phenylalanine, tryptophan, carotenoids, tyrosine, arginine, leucine [ 88 ] ST elevation myocardial infarction Plasma Ceramides, dihydroceramides, and sphingomyelins [ 69 ] Lung cancer Pleural effusions Phenylalanine, leucine, PC 35:0 and SM 44:3 [ 91 ] Serum Ceramides, PC and polyunsaturated acyl chains [ 92 ] Prostate cancer Urinary PS 18:1/18:1 and lactosylceramide (d18:1/16:0) [ 93 ] Benign prostate hyperplasia Urinary PC, PE, SM [ 31 ] Bipolar disorder Serum lysoPE 18: 0, lysoPE 14: 0, lysoPC 18: 0, and lysoPC 20: 1 [ 73 ] Schizophrenia Depressive disorder Chromochromic leukogystrophy …”
Section: How Potential Of Metabolomics Of Extracellular Vesicles For ...mentioning
confidence: 99%
“…The research articles of this Special Issue extend the knowledge about EVs for a broad range of cancer subtypes, such as glioblastoma [ 13 ], synovial sarcoma [ 14 ], pancreatic cancer [ 15 ], ovarian cancer [ 16 ], lung cancer [ 17 ], esophageal squamous cell carcinoma [ 18 ] and breast cancer [ 19 ].…”
mentioning
confidence: 99%
“…Smolarz et al compared lipid profiles of serum-derived small EVs from participants of a prospective lung cancer screening study with three groups of participants: without lung lesions, with benign lung nodules, and with screening-detected lung cancer [ 17 ]. Differences identified between groups were only of limited power with possible applicability as biomarker in the early detection of lung cancer.…”
mentioning
confidence: 99%